Islamic Moral Education and Spiritual Development as a Strategy for Preventing Deviant Behavior (Moral Deviation) - Fathurrahman; Jasiah (Faculty of Teacher Training and Education, Palangka Raya University, Central Kalimantan, Indonesia. Pos Code 73112, 2025)
This article explains key moral principles such as honesty, fairness, responsibility, and empathy, and how these principles form the foundation for developing positive social behavior. The aim is to describe what constitutes moral and behavioral deviation and what its impacts are. Methods This research uses a library research approach to collect data and information related to morals and deviant behavior in society. The analysis was conducted through a literature review that included scientific publications, books, and documents related to societal moral behavior. Research results show that morals are principles and values ​​that guide individuals in determining the rightness or wrongness of an action. Deviant behavior, on the other hand, refers to actions that deviate from prevailing societal norms and rules. Factors contributing to deviant behavior include social pressure, lack of moral education, and psychological factors. The negative impacts of deviant behavior on individuals and society are also outlined, such as the breakdown of trust, increased crime, and reduced social welfare. Real-life case studies of deviant behavior, such as corruption and violence, are used to illustrate the consequences of such actions and the resulting moral implications. The article concludes that a sound understanding of morality and its implications can help prevent deviant behavior, thus creating a more just, peaceful, and harmonious society.